IoT System for Monitoring Protection IED Switch Status - Muhammad Abdullah (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2026)
The reliability of protection systems in transmission networks depends on the readiness of devices, particularly the switch status that governs trip functions during a fault. In many substations, monitoring is still manual, conducted via panel checks or photos, which can lead to delays and misconfigurations, especially after maintenance. This risks protection unreadiness, causing operational delays or trip failures. This research develops an IoT-based system to monitor the status of protection switches, ensuring real-time readiness. The system reads IED coil registers via Modbus TCP, processes data using Node-RED, and displays results on a Node-RED UI dashboard. Results show the system reads switch status with 100% communication success. Status changes are detected in 0.2–0.3 seconds, matching the 0.5-second polling interval. Tests conducted on four IED test scenarios demonstrated full conformity between the IED status and the dashboard. All five protection channels per IED were read without discrepancies, and the dashboard handled parallel IED updates without data loss. This demonstrates that the system can replace slow and error-prone manual methods. This IoT system enhances protection reliability and supports efficient subsystem management. The implication is that this digital monitoring can be implemented without additional SCADA infrastructure.